Pendampingan Penataan Ruang Pemukiman Melalui Kuliah Kerja Nyata Tematik di Desa Lonthor - Grizelda Dominique Joris; W. D. Nanlohy; Resky Prafitri; Kreisson Pisty Larwuy (EMPOWERMENT: Journal of Community Practice, 2025)
Rural spatial planning is a crucial aspect in efforts to control land use so that management can be carried out optimally and sustainably. The preparation of a village settlement spatial plan is expected to be one of the solutions to address the challenges of village space and land utilization, especially future challenges such as the need for residential land by village residents. The approach used is a descriptive qualitative approach aimed at identifying factors within an area, such as physical and non-physical conditions, which will later serve as the basis for generating design ideas (alternative designs). Data collection techniques were carried out through field observation and obtained from relevant sources such as literature studies, government sources, and articles related to this community service activity. The analytical techniques used include site analysis and design, which form the foundation for developing planning concepts and conducting discussions with the community to obtain feedback on the proposed spatial concept. The analysis results show that planning using the Redevelopment concept in the form of Homestays is appropriate to be implemented in Lonthor Village. The results were discussed with the village community, and while they accepted the design, they also raised obstacles and challenges regarding its implementation if it were to be realized.